Analysis of physical activity and self-confidence of students of humanitarian faculties from Kaunas (Lithuania) - Ivaskiene V.; Skyriene V.; Cepelioniene J. (Kharkov National Pedagogical University, 2013)
We studied the self-confidence of students depending on their physical activity and attendance mandatory and not mandatory physical training. On the basis of the questionnaire Zaborskisa A. (1997) developed a questionnaire that allows you to set the level of physical activity of students. In identifying the confidence of students in themselves used the technique Stolina B. (1983). An anonymous questionnaire was attended by 249 first-year students. 144 students from universities, training program which provides for the mandatory physical education. 105 students from universities in which physical training are not required. Found that physically active and involved in sports and attending mandatory physical education students are more confident.